Effects of dietary arginine supplementation on growth, biochemical, and immunological responses of common carp (Cyprinus carpio L.), stressed by stocking density - Seyyed Morteza Hoseini (2019)
© 2019 Elsevier B.V. The present study aimed to investigate interaction effects of dietary arginine and stocking density on common carp (Cyprinus carpio) growth performance, stress response, innate immunity and immune gene expression. Three diets with deficient (4.1% of dietary protein; DA), optimum (5.3% of dietary protein; OA) and surplus (8.1% of dietary protein; SA) arginine levels were formulated. The diets were offered for 30 days to common carp reared at two different stocking densities, 10 or 20 g/L. Then blood leukocyte count, and plasma cortisol, glucose, total protein, globulin, total immunoglobulin (Ig), lysozyme and complement (ACH50), and head kidney interleukin-1 beta (IL-1beta), interleukin-8 (IL-8) and tumor necrosis factor-alpha (TNF-a) were determined. Results showed that increased stocking density led to decreased growth performance; similarly, both DA and SA groups had significantly lower growth performance compared to the OA group. Increased stocking density led to increased plasma cortisol, glucose, lysozyme, proteins and ACH50 and decreased plasma total Ig and blood WBC, and the head kidney’ cytokine genes expression. Both DA and SA groups had significantly higher plasma cortisol and glucose, and lower plasma lysozyme, proteins, ACH50, and head kidney's cytokine gene expression compared to the OA treatment; the SA group had more adverse effects on these parameters than the DA group. Dietary arginine at optimum level significantly inhibited the stress-induced cortisol and lysozyme elevation and mitigated the stress-induced IL-1beta and IL-8 genes down-regulation. In conclusion, dietary arginine deficient or surplus levels significantly impair common carp growth performance and health conditions. Moreover, surplus dietary arginine level has no benefit on the fish growth and health under high stocking density condition.